Teaching Literature in The Class - Syahruni Junaid (Al-Hikmah Journal for Religious Studies, 2012)
Teaching literature in the classroom emphasis on improving students ability through the presentation of extracts of novels and short stories through their literary development. In addition, the potential of literary texts carry for the students' critical ability development and personal growth. There are some forms of exercises that can be applied in the classroom by using all forms of literature